An American editor in early revolutionary China : John William Powell and the China weekly/monthly review - O'Brien, Neil L., 1947- (Routledge, 2003)
This is a study of Sino-American relations and the editorial policy of the China Weekly Review/China Monthly Review, published in Shanghai by John William Powell during the Chinese Civil War.
Keywords: Powell, John William, -- 1919-2008.; China weekly review.; China monthly review.; Powell, John William; United States -- Foreign relations -- China.; China -- Foreign relations -- United States.; United States -- Foreign relations -- 1945-1953 -- Press coverage.; China -- History -- Civil War, 1945-1949 -- Press coverage.; Newspaper editors -- United States -- Biography.; Newspaper editors -- China -- Shanghai -- Biography.; États-Unis -- Relations extérieures -- Chine.; Chine -- Relations extérieures -- États-Unis.; États-Unis -- Relations extérieures -- 1945-1953 -- Couverture de presse.; Chine -- Histoire -- 1945-1949 (Guerre civile) -- Couverture de presse.; Rédacteurs en chef -- Chine -- Shanghai -- Biographies.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Diplomatic relations; Newspaper editors; Press coverage; China; China -- Shanghai; United States; 1945-1953; Biographies; History; Biographies.